Optimising endotracheal length in adult cats: a retrospective CT study. Issue 8 (August 2022) - Rodriguez, Alfonso; Medina-Serra, Roger; Plested, Mark J; Veres-Nyeki, Kata
Objectives: The aim of this study was to determine the maximal endotracheal insertion length by measuring the larynx to carina (L–C) distance by means of CT. An additional objective was to establish certain anatomical landmarks to optimise the process of endotracheal intubation (ETI). Methods: Head, neck and thoracic CT images from adult cats at a single referral hospital between 2013 and 2020 were retrospectively evaluated. After standardising and identifying key markers (larynx, carina and first rib) the L–C, larynx to first rib (L–1R) and first rib to carina (1R–C) distances were measured. Results: Forty-five adult cats were enrolled in the study, from which a total of nine different breeds were identified. The L–C distance was 14.3 ± 1.1 cm. This was longer in male (14.7 ± 1.1 cm) than in female cats (13.5 ± 0.7 cm). The first rib (1R) was 8.8 ± 0.7 cm from the larynx and the mean 1R–C distance was 5.4 ± 0.7 cm. The carina was found within the fifth intercostal space in 93.3% (n = 42) of the cats. Conclusions and relevance: The process of ETI in adult cats may be guided by using the L–C and L–1R distance for a maximal and optimal endotracheal tube introduction, respectively. In addition, the maximal insertion length may be guided by estimating the position of the carina parallel to the fifth intercostal space.